amorfide
  • amorfide
I need to know how to integrate this
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
amorfide
  • amorfide
1 Attachment
anonymous
  • anonymous
use partial fractions here\[\frac{3x+4}{(x^2+4)(x-3)}=\frac{Ax+B}{x^2+4}+\frac{C}{x-3}\]and find A,B and C
carson889
  • carson889
Split using partial fractions: \[\frac{ 3x+4 }{ (x ^{2}+4)(x-3) } = \frac{ A }{ x-3 } + \frac{ Bx + C}{ (x ^{2} + 4) } = \frac{ A(x^{2} +4)+(Bx+C)(x-3) }{ (x ^{2}+4)(x-3) }\] Set equal to 3, looking at just numerator: \[3*3 + 4 = 13 = A(9+4) + (3B+C)(0) = 13A \rightarrow A = 1\] Set x equal to 0: \[0 + 4 = 4 = 4A + C \rightarrow 4 = 4+C \rightarrow C = 0\] Set x equal to 1: \[3 + 4 =A(1+4) + (B+C)(1-3) = 5A -2B -2C \rightarrow 5 - 2B - 0 \rightarrow 2 = -2B \rightarrow B = -1\] Therefore: \[\frac{ 3x+4 }{ (x ^{2}+4)(x-3)} = \frac{ 1 }{ x-3 } - \frac{ x }{ x ^{2} + 4 }\] Now integrate those.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

amorfide
  • amorfide
thank you very much, you have no idea how much i love you xD
carson889
  • carson889
No problemo The integral of 1/(x-3) is ln(x-3) and the integral of -x/(x^2 + 4): u-sub: u = x^2 + 4, du = 2x dx \[\frac{ -1 }{ 2 } \int\limits_{}^{}\frac{ 1 }{ u }du = \frac{ -1 }{ 2 }\ln(u) = \frac{ -1 }{ 2 }\ln(x ^{2}+4)\] \[\left( \ln(2-3) - \frac{ 1 }{ 2 }\ln(4+4) \right)-\left( \ln(0-3) - \frac{ 1 }{ 2 }\ln(0+4) \right) \] \[= \ln(-1)-\frac{ 1 }{ 2 }\ln(8)-\ln(-3)-\frac{ 1 }{ 2 }\ln(4) = \ln(\frac{ 1 }{ 3\sqrt{2} })\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.